2022
DOI: 10.1039/d2tb00422d
|View full text |Cite
|
Sign up to set email alerts
|

Ratiometric imaging of butyrylcholinesterase activity in mice with nonalcoholic fatty liver using an AIE-based fluorescent probe

Abstract: Butyrylcholinesterase (BChE) is an essential human biomarker which related to liver and neurodegenerative diseases, it is of great significance to develop a fluorescent probe that can image BChE in vitro...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(13 citation statements)
references
References 56 publications
0
13
0
Order By: Relevance
“…Effective monitoring of the physiological progression of ALI is crucial for early theranostics to reduce its high mortality rate. Recent evidence suggests that the upstream–downstream linkages of esterase could be a critical factor for physiology studies of various diseases in vivo. A few studies have been reported and validated for evaluating the dynamic changes of esterase in the lungs. , Given the above, the physiological progression of ALI can be further determined by detecting the dynamic changes of esterase. Accordingly, the novel probe FJH-C was rationally designed and synthesized by introducing the response group (cyclopropanecarbonyl chloride) at the phenolic hydroxyl position of FJH (Figure a) .…”
Section: Results and Discussionmentioning
confidence: 99%
“…Effective monitoring of the physiological progression of ALI is crucial for early theranostics to reduce its high mortality rate. Recent evidence suggests that the upstream–downstream linkages of esterase could be a critical factor for physiology studies of various diseases in vivo. A few studies have been reported and validated for evaluating the dynamic changes of esterase in the lungs. , Given the above, the physiological progression of ALI can be further determined by detecting the dynamic changes of esterase. Accordingly, the novel probe FJH-C was rationally designed and synthesized by introducing the response group (cyclopropanecarbonyl chloride) at the phenolic hydroxyl position of FJH (Figure a) .…”
Section: Results and Discussionmentioning
confidence: 99%
“…Compared with conventional fluorescent probes, AIEgens show great advantages in the imaging of metabolic diseases. 91,171,172 To overcome the strong hydrophobicity that limits the efficiency of lipid-specific fluorophores for in vivo labeling in metabolic diseases, Liu et al synthesized two AIEgens (TPACN and TPAPhCN) with a typical D-A structure. Triphenylamine (TPA) served as the electron donor, while the dicyanovinyl group served as the electron acceptor.…”
Section: Metabolic Disease Bioimagingmentioning
confidence: 99%
“…It is associated with various diseases, such as liver disease, diabetes and Alzheimer’s disease [ 94 ]. Recently, Xiang et al designed a ratiometric fluorescent probe (TB-BChE) for imaging of BChE based on AIE mechanisms [ 95 ]. The TB-BChE probe showed a low intramolecular charge transfer effect because of the poor electron-donating ability of the ester group.…”
Section: Cholinesterasesmentioning
confidence: 99%